Progress of fluorescence imaging in lymph node dissection surgery for prostate and bladder cancer - Xu, Mingquan; Li, Panpan; Wei, Jinzheng; Yan, Pengyu; Zhang, Yunmeng; Guo, Xinyu (Frontiers in Oncology, 2024)
Fluorescence imaging is a relatively new imaging method used to visualize different tissue structures to help guide intraoperative operations, which has potential advantages with high sensitivity and contrast compared to conventional imaging. In this work, we review fluorescent contrast agents and devices used for lymphatic system imaging. Indocyanine green is the most widely utilized due to its high sensitivity, specificity, low background fluorescence, and safety profile. In prostate and bladder cancer lymph node dissection, the complex lymphatic drainage can result in missed metastatic nodes and extensive dissection increases the risk of complications like lymphocele, presenting a significant challenge for urologists. Fluorescence-guided sentinel lymph node dissection facilitates precise tumor staging. The combination of fluorescence and radiographic imaging improves the accuracy of lymph node staging. Multimodal imaging presents new potential for precisely identifying metastatic pelvic lymph nodes.